A facile surfactant-assisted synthesis of graphene oxide/zinc oxide catalyst for the degradation of methylene blue dye - Mior Mohd Hasri Abdul Aziz (Tanjong Malim, 2024)
A facile surfactant-assisted synthesis of graphene oxide/zinc oxide catalyst for the degradation of methylene blue dye by Mior Mohd Hasri Abdul Aziz